PENGARUH WARNA BUNGA TANAMAN KENIKIR TERHADAP KEANEKARAGAMAN SERANGGA PADA TANAMAN CABAI (Capsicum Annum L.) - RAHMAN, ABDUL; PAKKI, TERRY; ULFA, NUR ISNAINI; HUTTNI, LITA OKTAFIANA (Jurnal Agroteknos, 2022)
Excessive use of insecticides will have a negative impact on the development of ecosystem and the environment, kill non-target insects and kill natural enemies and pollinating insects. One solution to control pests on chili plants is to engineer ecology using refugia plants. Kenikir is a refugia plant that plays an important role in increasing the population of useful insects such as predators and pollinators. This study aims to determine the effect of flower color of kenikir plants on insect diversity in chili plants (Capsicum annum L.). This research was observed on kenikir plants planted around chili plants with the color treatment of kenikir flowers, namely yellow kenikir (C1), orange kenikir (C2) and pink kenikir (C3). The treatment was repeated 6 times so that there were 18 units of observation plots. The variables observed were the number of insect species and their roles, diversity index, species dominance index and evenness index. Observational data were analyzed by simple tabulation to see differences between tretments. The results showed that there were various types of insects that landed on the kenikir flower in different flower colors, but the diseversity index value is in the low category or ≤ 2. The highest index value of diversity and insect population was obtained in the treatment of yellow flowers, then orange and the lowest was in pink flowers.